Broad-spectrum anti-HIV activity and high drug resistance barrier of lipopeptide HIV fusion inhibitor LP-19 - He, Lin; Wang, Chen; Zhang, Yuanyuan; Chong, Huihui; Hu, Xiaoyan; Li, Dan; Xing, Hui; He, Yuxian; Shao, Yiming; Hong, Kunxue; Ma, Liying (Frontiers in Immunology, 2023)
HIV lipopeptide fusion inhibitor 19 (LP-19) has showed potent antiviral activity. However, there is still limited information in LP-19 broad-spectrum of antiviral activity against different subtype clinical isolates and drug resistance barrier. The viral features are 43 CCR5 and 4 CCR5/CXCR4 tropisms respectively, and different subtypes with 6 subtype B’, 15 CRF01_AE, 14 CRF07_BC, 2 CRF08_BC and 10 URF strains. These viruses were used to detected and analyze the inhibitory activities of LP-19. The average exhibition IC50 value of LP-19 was 0.50 nM. The mean values of B’, CRF01_AE, CRF07_BC, CRF08_BC and URF strains were respective 0.76 nM, 0.29 nM, 0.38 nM, 0.85 nM, and 0.44 nM concentration. C34 and Enfuvirtide (T-20) were fusion inhibitors and compared on the corresponding strains Simultaneously. The antiviral activity of LP-19 were 16.70-fold and 86.00-fold higher than that of C34 and T-20, respectively. The antiviral activity of LP-19, C34 and T-20 were further detected by HIV-1 NL4-3 strains, showed IC50 were 0.15±0.01 nM, 1.02±0.19 nM, and 66.19±20.73 nM respectively. IC50 of LP-19 was about 7-fold and 449-fold higher comparing to C34 and T-20. NL4-3 strains were exposed to increasing concentrations of LP-19 though MT-2 cells culture. The A243V mutation site was identified at weeks 28, 32, 38, 39 of the cells culture in gp41 CP (cytoplasmic domain) region. Then, the antiviral activities of LP-19 against HIV-1 NL4-3 strains and HIV NL4-3/A243V strains were evaluated. LP-19 showed 1.3-fold activity to HIV NL4-3/A243V strains than before mutation. LP-19 did not show true drug resistance site when the drug concentration reached 512-fold of the initial concentration under the drug pressure for up to 39 weeks. It shows that LP-19 has a broad-spectrum antiviral activity and high drug resistance barrier of HIV lipopeptide fusion inhibitor LP-19.